The exotic legume tree species, Acacia mearnsii, alters microbial soil functionalities and the early development of a native tree species, Quercus suber, in North Africa - Boudiaf, I.; Baudoin, E.; Sanguin, H.; Beddiar, A.; Thioulouse, J.; Galiana, A.; Prin, Y.; Le Roux, C.; Lebrun, M.; Duponnois, R. (Soil Biology and Biochemistry, 2013)
Acacia mearnsii is one of the most planted Australian Acacia around the world but is known to be highly invasive, threatening native habitats by competing with indigenous vegetation. The introduction of this species in the Algerian El Kala Biosphere reserve led to the invasion of natural formations to the detri- ment of Quercus suber, a native tree species.We hypothesized that shifts in soil microbial functions and ectomycorrhizal (EcM) fungal community structure triggered by this exotic Acacia species might correlate with a decrease of the early growth of Q. suber. Soil samples were thus collected from 3 different sites where the exotic specieswas at different stages of invasion in the Algerian El Kala Biosphere reserve, (i) a Q. suber forest free of A. mearnsii (site S1), (ii) a Q. suber/A. mearnsii mixed forest where the Australian Acacia has been recently detected (site S2) and (iii) pure stands of A. mearnsii formed more than 20 years ago (site S3). Plant growth, EcM community structure associated with Q. suber roots and soil microbial functionalities were assessed for 6 month-old cultures of Q. suber in glasshouse conditions. The results clearly demonstrated a strong deleterious impact of A. mearnsii invasion level on soil chemical characteristics, microbial functions and EcM community structure and colonization, correlated to a decrease in the early growth of Q. suber seedlings. The current study gives new insights into both the negative impact of exotic species on soil functioning and their effect on indigenous vegetation growth. These results may be used as a basis for improving the conservation practices of native tree species in such degraded areas as a complement of ecological strategies using indigenous ectotrophic early- successional shrub species (eg. Cistus spp.) that our findings have shown to promote EcM multiplica- tion and the early growth of native tree species. 
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Acacia mearnsii; ectomycorrhiza; exotic invasive plant; Soil microbial community